Blood Cancer and the Heart: Light Chain Cardiomyopathy in Refractory Multiple Myeloma - Abdulbaril Olagunju; Chandana Shekar; Michael Morris; Anantharam Kalya; Farouk Mookadam; Samuel Unzek (Case Reports in Cardiology)
We report a case of a 57-year-old woman with a history of multiple myeloma (MM) and light chain (AL) amyloidosis who presented due to worsening dyspnea on exertion. Her MM has been refractory to multiple chemotherapy regimens and two autologous bone marrow transplantation. Diagnostic evaluations including serum kappa and lambda chains, echocardiogram, pyrophosphate cardiac scan, and cardiac magnetic resonance were indicative of a progression to AL cardiomyopathy. Addition of daratumumab to her regimen appeared to ameliorate the progression of AL cardiomyopathy. However, it was stopped due to adverse effects of pancytopenia and allergic reactions including skin rash and hives. She was hospitalized for heart failure exacerbation and died approximately 2 months following the discontinuation of daratumumab. This case highlights the late presentation of AL cardiomyopathy in refractory MM.